PROPUESTA DE UN SISTEMA DE RECOMENDACIÓN HIBRIDO SEMÁNTICO DE OBJETOS DE APRENDIZAJE EN EL ÁREA DE EDUCACIÓN AMBIENTAL BASADO EN LINKED DATA (2023)
This paper proposes an architecture for the recommendation of learning objects in the area of environmental education using the standard LOM whit the purpose of represent educational resources in the area.